Biologically confirmed sexually transmitted infection and depressive symptomatology among African-American female adolescents. Issue 1 (3rd February 2006) - Salazar, L F; DiClemente, R J; Wingood, G M; Crosby, R A; Lang, D L; Harrington, K
Abstract : Objective: To determine prospectively the relation between sexually transmitted infection (STI) diagnosis and depressive symptomatology. Methods: Secondary data analyses were performed on 175 sexually active African-American female adolescents, who were recruited from high risk neighbourhoods in Birmingham, Alabama, United States. Results: ANCOVA was used to compare adolescents who tested positive with adolescents who tested negative on three waves of depressive symptom scores, controlling for age. The STI positive group had higher depressive symptom levels at 6 months relative to the STI negative group. This result was moderated by baseline depressive symptom levels: for adolescents above the clinical threshold, the STI negative group experienced a decrease in symptoms at 6 months whereas the STI positive group maintained the same level. For adolescents below the clinical threshold, there were no changes in depressive symptom levels regardless of diagnosis. Conclusions: Receiving an STI diagnosis may affect depressive symptomatology for those at risk for depression. Screening for depression in settings that provide STI testing and treatment may be warranted for this population.